Differential Early in vivo Dynamics and Functionality of Recruited Polymorphonuclear Neutrophils After Infection by Planktonic or Biofilm Staphylococcus aureus - Abdul Hamid, Aizat Iman; Cara, Andréa; Diot, Alan; Laurent, Frédéric; Josse, Jérôme; Gueirard, Pascale (Frontiers in Microbiology, 2021)
Staphylococcus aureus is a human pathogen known for its capacity to shift between the planktonic and biofilm lifestyles. In vivo, the antimicrobial immune response is characterized by the recruitment of inflammatory phagocytes, namely polymorphonuclear neutrophils (PMNs) and monocytes/macrophages. Immune responses to planktonic bacteria have been extensively studied, but many questions remain about how biofilms can modulate inflammatory responses and cause recurrent infections in live vertebrates. Thus, the use of biologically sound experimental models is essential to study the specific immune signatures elicited by biofilms. Here, a mouse ear pinna model of infection was used to compare early innate immune responses towards S. aureus planktonic or biofilm bacteria. Flow cytometry and cytokine assays were carried out to study the inflammatory responses in infected tissues. These data were complemented with intravital confocal imaging analyses, allowing the real-time observation of the dynamic interactions between EGFP+ phagocytes and bacteria in the ear pinna tissue of LysM-EGFP transgenic mice. Both bacterial forms induced an early and considerable recruitment of phagocytes in the ear tissue, associated with a predominantly pro-inflammatory cytokine profile. The inflammatory response was mostly composed of PMNs in the skin and the auricular lymph node. However, the kinetics of PMN recruitment were different between the 2 forms in the first 2 days post-infection (pi). Two hours pi, biofilm inocula recruited more PMNs than planktonic bacteria, but with decreased motility parameters and capacity to emit pseudopods. Inversely, biofilm inocula recruited less PMNs 2 days pi, but with an “over-activated” status, illustrated by an increased phagocytic activity, CD11b level of expression and ROS production. Thus, the mouse ear pinna model allowed us to reveal specific differences in the dynamics of recruitment and functional properties of phagocytes against biofilms. These differences would influence the specific adaptive immune responses to biofilms elicited in the lymphoid tissues.